Aspek Hukum Masalah Pengungsi Internasional - Suwardi, Sri Setianingsih (Indonesian Journal of International Law, 2004)
Under international law, a State may refuse to accord entry permit to its territory for aliens. However, there is always a possibility that under certain circumstances an alien enters a State without having any permit as it is in the case of refugee. Refugees have the right to be given protection as attached to their refugee status. The refugee rights for protection by the host state is included in various regional and international treaties such as Conventin relating the Status of Refugee 1951 and Protocol relating the Status of Refugee 1967. In reality, the refugee problem is more complex as it relates to legal issues such as those in regard to asylum seeker, stateless persons, illegal immigrant, and extradition. In many cases, there are difficult problems in deciding whether or not an individual or a group of aliens to be given the refugee status. In an effort to solve the refugee problems around the world, the United Nations established the United Nations High Commissioner for Refugee (UNHCR). The following article describes comprehensively the refugee problems faced the international community.